No strings attached: physiological monitoring of rhesus monkeys (Macaca mulatta) with thermal imaging - Ioannou, Stephanos; Chotard, Hélène; Davila-Ross, Marina (Frontiers in Behavioral Neuroscience, 2015)
Methodological challenges make physiological affective observations very restrictive as in many cases they take place in a laboratory setting rather than the animals’ natural habitat. In the current study using Infrared Thermal Imaging we examine the physiological thermal imprints of 5 macaques. The monkeys were exposed in 3 different experimental scenarios. Playing with a toy, food teasing as well as feeding. It was observed that during teasing the temperature of the region surrounding the eyes was higher than play as a result of rapid saccades directed at the food. Compared to play and teasing, a lower temperature accompanied feeding on the upper lip, nose and orbital region suggesting elevated levels of distress. These findings prove that thermal imaging is a reliable method of physiological monitoring the subject at a distance while preserving a semi-experimental setting.